Cardiovascular complications in hemodialysis patients: current approaches to prolong and improve quality of patients’ life - F. O. Prusskiy (Ukrainian Journal of Nephrology and Dialysis, 2019)
Cardiovascular complications are a leading cause of morbidity and mortality in dialysis patients. Cardiovascular mortality is more than 40% of the total mortality in this cohort of patients. Recently, there has been an increase in publications on the role of uremic toxins, including “middle molecules”, in the development and progression of cardiovascular complications in dialysis patients.Conventional low-flux (LF) hemodialysis well removes small molecular weight uremic toxins not bound with protein. Evidence for the role of "middle molecules" in the development of many complications, including cardiovascular complications, has contributed to the emergence and development of such dialysis therapy methods as high-flux (HF) hemodialysis, hemofiltration (HF) and hemodiafiltration (HDF).Further evolution of membrane technology has led to the development of protein-leaking membranes or super-flux or high cutoff (HCO) membranes. These membranes are capable of removing molecules in excess of the molecular weight of albumin. The use of these membranes is limited because of the risk of hypoalbuminemia.Today, the closest approximation to the natural glomerular membrane is the so-called Middle Cut-Off (MCO) membrane. The use of MSO membranes is implemented in a new method of dialysis therapy - expanded hemodialysis (HDx). The method is defined as a treatment where diffusion and convection are conveniently combined inside a hollow-fibre dialyser equipped with an MCO membrane. A standard hemodialysis machine is used for the HDx. Increased removal of large medium molecules in HDx may lead to an improvement of clinical outcomes, including a decrease of the cardiovascular events incidence, an all-cause and cardiovascular mortality reduction in dialysis patients.